2010
DOI: 10.2139/ssrn.1679764
|View full text |Cite
|
Sign up to set email alerts
|

The Development of RIA in the European Union: An Overview

Abstract: The European Commission has successfully managed to adopt and implement ex ante impact assessment procedures since 2003, and available data show that the IA documented are of increasingly good quality. Even though margins for improving the European Commission IA system persist, other EU institutions and almost all EU member states significantly lag behind in terms of IA implementation. The experience of past research projects, including the European Network for Better Regulation and the recent OECD EU15 projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…13 This Board found that impact assessments (for all sectors) with a focus on environmental or climate policy objectives increased to 38% of all cases from an average of 23% in 2017-19. In 2020, 74% of all impact assessments quantified benefits and 83% assessed costs (Regulatory Scrutiny Board of the European Commission, 2020 [75]).…”
Section: Regulatory Impact Assessment (Ria)mentioning
confidence: 99%
“…13 This Board found that impact assessments (for all sectors) with a focus on environmental or climate policy objectives increased to 38% of all cases from an average of 23% in 2017-19. In 2020, 74% of all impact assessments quantified benefits and 83% assessed costs (Regulatory Scrutiny Board of the European Commission, 2020 [75]).…”
Section: Regulatory Impact Assessment (Ria)mentioning
confidence: 99%
“…IFC Better Regulation for Growth program, Regulatory Governance in Developing Countries, available online at: http://www.fias.net/ifcext/fias.nsf/AttachmentsByTitle /BRG_PapersWhatisit/$FILE/RegulatoryGovinDevCountries.pdf See also i.a. Renda, A. (2010), The Development of RIA in the European Union, paper presented at the World Bank Regulatory Reform Conference in Belgrade (Serbia), 13-14 September 2010. comparison between the US and EU agenda and better regulation strategy is performed more in detail.…”
Section: What This Thesis Is Notmentioning
confidence: 99%
“…First, the regular production of IAs -both the European Commission Directorates-General (DGs) and British departments -are heavy producers of assessments compared to the average EU member state. Second, there are oversight bodies (Wiener & Alemanno, 2010;Renda, 2010). The UK Regulatory Policy Committee (RPC), established in 2009, follows the experience of other European countries (like Germany, Sweden and the Netherlands) and the European Commission with oversight bodies.…”
Section: Introductionmentioning
confidence: 99%